Diferenciação genética de populações do gênero Neoplecostomus (Teleostei: Loricariidae) da bacia do Alto Rio Paraná - Lucena, Ana Luisa Monezi (2010)
The Neotropical freshwater ichthyofauna comprises a rich diversity of fish. The taxonomic, ecological and economical are needed for identification and conservation of this species Neoplecostomus and other fish species. This study aimed to analyze the genetic variability of eight populations of the genus Neoplecostomus of taxonomic status is not defined and compared with a population of species already described as Neoplecostomus corumba. For this we used the technique of isoenzyme electrophoresis in starch gel for the analysis of six (G3pdh, GPI, LDH, IDH, MDH and PGM) enzyme systems. Were observed in 10 loci and 24 alleles, four alleles were unique, two present in the population of Cachoeira (Gpi-B (b) and Idh (b)) and other populations of Taquari (Gpi-A (e)) and of Espraiado (Gpi-A (a)). All populations showed polymorphic loci, except the population of Casca D'Antas. The average number of alleles per locus to ranged from 1.8-1.0. The average of the index FIS (0.5621) and FIT (0.8716) indicated the homozygote excess and the value of FST = 0.7067 indicated that the populations are genetically too different from each other. Nei's Genetic Identities and genetic distances estimated demonstrate that some of them are enough different to be considered distinct species. UPGMA dendrogram demonstrated that the populations are grouped into three sets, Cachoeira+N.corumba+Espraiado, Piranguçu+Jaguari+Monjolinho+Casca D'Antas, and Carandaí+Tamborete. We conclude that the methods used were effective for differentiation of populations reflecting a strong indication of the presence of at least two different Neoplecostomus corumba among the regions analyzed the upper of the Paraná River basin.